A simple, cost effective method for isolation and transportation of Leishmania parasites - Ihalamulla, R. L.; Rajapaksa, U. S.; Siriwardena, H V Y D; Chance, M.; Karunaweera, N. D. (Sri Lanka Medical Association, 2009)
Abstract Isolation and propagation of Leishmania parasites using conventional culture methods are difficult, especially under field conditions. Transportation of live parasites requires the maintenance of low temperatures, which increases the cost considerably. The present study demonstrates that monophasic micro capillary culture is a simpler, more economical and better alternative to using conventional Evan’s modified Tobie’s medium to isolate and transport the Leishmania parasite over long distances without the use of temperature control methods
Keywords: cost effective; transportation; Leishmania; Sri Lanka